Marketing Mix Dan Brand Image Terhadap Keputusan Pembelian Kain Tenun Sebagai Upaya Mempertahankan Eksistensi Produk Lokal - Ovriyadin; Sri Ernawati (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to determine and analyze the influence of marketing mix and brand image as a marketing strategy. Before marketing activities occur, it is important for business actors, in this case weaving SMEs in Bima City, to know buyer behavior first to know what strategies will be implemented to market woven products. Determining a marketing strategy through a marketing mix that is right on target and increasing the brand image of woven products can increase consumer purchasing decisions as well as an effort to maintain the existence of local products in Bima City. The type of research in this research is quantitative. The method used in this research is an explanatory survey approach, namely through collecting data from respondents. The research instrument used was a questionnaire with a Likert scale containing a list of questions for respondents to answer. The sample in this study amounted to 200 people. Then, to test the research, it was carried out with the help of Smart Partial Least Square (SmartPLS) Software. The research results marketing mix and brand image have a significant influence on the decision to purchase woven fabric as an effort to maintain the existence of local products in Bima City